Fallow Weed Control with Vida Tank Mixtures - R. S. Currie; P. W. Geier (Kansas Agricultural Experiment Station Research Reports, 2021)
The objective of the study was to compare Vida (pyraflufen) with various tank mix partners for glyphosate-resistant kochia control. Flixweed control was complete in fallow with all herbicides by 28 days after treatment. Kochia control was best when Vida was applied with glyphosate and Spartan. However, due in part to the extremely dry conditions, no treatment controlled kochia by more than 83% at 28 days after treatment, and kochia control began to decline after this 28 DAT.
Keywords: herbicide-resistant weeds